Penggunaan Pendekatan Culturally Responsive Teaching untuk Meningkatkan Motivasi dan Hasil Belajar Maharah Qiraah Siswa SMA Islam Malang - Rahman, Mohammad Fajar Fauzi; Ainin, Moh.; Al Nabiil, Ach Rifqiy (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2025)
This research aims to address the low motivation and reading proficiency (maharah qira’ah) among 11th-grade students at an Islamic Senior High School in Malang through the implementation of the Culturally Responsive Teaching (CRT) approach. The primary objective of this study is to improve students’ motivation to learn and Reading achievement by applying culturally relevant, student-centred instructional practices in the Arabic language learning context. The study employed a Classroom Action Research (CAR) model carried out in two cycles, each consisting of planning, action, observation, and reflection. The findings demonstrate a continuous improvement in both motivation and learning outcomes. Motivation increased from 72% in the pre-cycle to 75.1% in Cycle 1 and rose again to 78.1% in Cycle 2. Learning achievement followed a similar pattern: the pre-cycle mastery level reached 70%, dropped to 63.3% in Cycle 1 as students adapted to new learning strategies, and subsequently improved to 80% in Cycle 2 following strengthened implementation of CRT, enhanced scaffolding, and diversified learning media. These results indicate that culturally responsive practices significantly support students’ engagement, comprehension of Arabic texts, and overall academic performance. In conclusion, the consistent application of CRT effectively enhances learning motivation and Reading proficiency in maharah qira’ah. CRT is therefore recommended as a relevant and impactful instructional approach for Arabic language learning in culturally diverse classroom settings.